Pelatihan Peningkatan Kemampuan Literasi dan Numerasi di Sekolah Dasar Negeri Paninggaran Kuningan - Taufik, Azin; Anggar Titis Prayitno; Rahayu Syafari; Nuranita Adiastuty (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
The Merdeka Curriculum has been implemented in most schools in Indonesia, from PAUD to SMA. One form of assessment in this curriculum is the Computer-Based National Assessment (ANBK), which includes various types of assessments, including the Minimum Competency Assessment (AKM), learning environment surveys, and character surveys. In AKM, students are expected to master literacy and numeracy skills through questions with relatively long texts, which often make it difficult for many students to understand and solve the questions satisfactorily. As a solution, it is important for schools to intensively introduce the types of AKM questions to students and get them used to, both independently and in groups, solving numeracy literacy-based questions using interactive e-books. This community service program was carried out for one day at SDN Paninggaran Darma, Kuningan Regency, and focused on introducing AKM questions based on numeracy literacy. During the activity, grade 5 students showed that they were not familiar with the questions, so they still faced difficulties in solving the problems. The evaluation was conducted by asking students to complete 5 AKM questions based on numeracy literacy directly in class. The conclusion is that students already have an understanding of various types of Minimum Competency Assessment questions based on numeracy literacy and show an increase in their ability to solve questions in the moderate category. To improve students' numeracy literacy skills, routine efforts need to be made to introduce these questions during the daily learning process, so that they can better apply these skills in their daily lives. Suggestion: Students already understand various types of Minimum Competency Assessment questions that focus on numeracy literacy and show an increase in their ability to solve questions with a moderate level of difficulty. In order for students' numeracy literacy skills to continue to develop and be applied in their daily lives, it is important to continue